Fast Load Voltage Stability Index constrained PMU Placement for Complete Observability - Narayana, P.Lakshmi; Venkatesan, M.; Ravindra, S. (International Journal of Engineering and Technology, 2018)
This paper proposes a Fast Load Voltage Stability Index (FLVSI) constrained Binary Integer Programming (BIP) method for Phasor Measurement Unit placement at optimal locations in network to obtain complete observability. Every load bus of network is considered to sort out weak load bus from proposed FLVSI approach. PMUs are constrained to place at weak load buses using BIP approach for observability of network. Zero Injection (ZI) modeling is suggested to reduce PMU placement locations in network. Single line outage or PMU loss constraints are formulated for placement of PMUs. Bus Redundancy Index (BRI) is formulated and considered for every bus of network. With and without ZI modeling under normal and line outage cases is compared to present effectiveness of approach. IEEE –14- 30-and 57- bus networks are tested with MATLAB Programming and compared with other methods to show its effectiveness.